2017
DOI: 10.1038/s41598-017-14958-w
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput assessment of mechanical properties of stem cell derived red blood cells, toward cellular downstream processing

Abstract: Stem cell products, including manufactured red blood cells, require efficient sorting and purification methods to remove components potentially harmful for clinical application. However, standard approaches for cellular downstream processing rely on the use of specific and expensive labels (e.g. FACS or MACS). Techniques relying on inherent mechanical and physical properties of cells offer high-throughput scalable alternatives but knowledge of the mechanical phenotype is required. Here, we characterized for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 62 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…The first step to develop the label‐free strategy for purifying mRBC from the contaminant nucleated cells and free‐floating nuclei was to identify if there was a unique set of label‐free markers, such as cell size and deformability that would allow characterization of each of the subsets within the final product. These findings are detailed for donor III in Guzniczak et al (2017) and for donors I and II in Table S3 (for the convenience of the reader, also, data on donor III are included in STable 3). The study was further conducted here for cells from three different donors (see Figure 3 for exemplary data of one replica from each donor).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step to develop the label‐free strategy for purifying mRBC from the contaminant nucleated cells and free‐floating nuclei was to identify if there was a unique set of label‐free markers, such as cell size and deformability that would allow characterization of each of the subsets within the final product. These findings are detailed for donor III in Guzniczak et al (2017) and for donors I and II in Table S3 (for the convenience of the reader, also, data on donor III are included in STable 3). The study was further conducted here for cells from three different donors (see Figure 3 for exemplary data of one replica from each donor).…”
Section: Resultsmentioning
confidence: 99%
“…However, this was achieved by coculture with macrophages, making the protocol challenging to scale‐up (Goers, Freemont, & Polizzi, 2014). With lower enucleation rates, the presence of residual nucleated cells and expelled nuclei constitute a potential danger if intended for transfusion into patients (Bouhassira, 2008; Guzniczak et al, 2017). Undifferentiated nucleated cells can give rise to teratomas (benign tumors of differentiating cells) and teratocarcinomas (malignant metastatic tumors composed of highly proliferative cells; McGowan, Campbell, & Mountford, 2018), thus they have to be removed from the sample and require adequate purification approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These include endocytic pathways and proteins, mechanical properties, in addition to transcription factors and epigenetic modifiers. Recent reports have described using mechanical phenotyping as an label-free and efficient technique for large-scale purification of cells [33]. However, a better understanding of the interplay between mechanical properties and expression of stem cell-specific transcription factors is required before mechanical phenotyping can be used for large-scale purification of cells.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of erythropoiesis, the RBCs experience complete changes in cell composition and membrane mechanical properties during the journey of RBC production from the immature pronormoblasts to the mature biconcave discocytes [108]. Studies have shown that measurements of membrane mechanical attributes of the developing RBCs indicate the structural and functional maturation of the membrane skeleton [103].…”
Section: Evaluation Of Rbcs Developing and Functioningmentioning
confidence: 99%
“…Immature RBCs experience dramatic changes in shape, cellular composition, and membrane mechanical and physical properties throughout the erythropoietic process [103]. The quantitative evaluation of the stiffness of the nucleated and enucleated RBCs during maturation enables the direct evaluation of the development of membrane skeleton [108]. Mature human red blood cells (RBCs) are unique mammalian cells in biconcave shape (typically 6-8 µm in diameter and 2 µm in thickness) that contain no nucleus or subcellular metabolic structures [130].…”
Section: Evaluation Of Rbc Membrane Deformationmentioning
confidence: 99%